A Mobile Border: Cossack Maneuvers in the Context of Colonization (the Late 16th to the Early 17th Century) - A. V. Golovnev (Tractus Aevorum, 2015)
The Cossacks personified a “mobile border” in the southern Russian periphery (ukraina), one that maneuvered between the Muscovite state, the Polish Lithuanian Commonwealth, the Crimean Khanate, and the Nogai Horde. In the Field (Pole), where free and servant (sluzhilye) Cossacks came into contact, Russian military colonization moved south along Tatar routes (sakma) as part of an “expansion of defense” waged by Cossack bands, cordons, and fortresses. In the Time of Troubles in the early seventeenth century, the Cossacks turned their expansion back toward Moscow, and the “mobile border” struck the capital. By sponsoring and supporting false tsars, Cossacks both disrupted and compelled the Muscovite state from 1605 to 1611. They played a key role in Michael Romanov‟s election though a remarkable status reversal immediately occurred as a result: by swearing an oath to Romanov, the free Cossacks found themselves in the tsar‟s service.